Nutritional and bioactive profile of different parts of Carica papaya L. in relation to thrombocytopenia. Issue 1 (31st December 2022) - Nouman, Muhammad; Niaz, Bushra; Saeed, Farhan; Arshad, Muhammad Umair; Anjum, Faqir M.
ABSTRACT: The aim of the present study was to elucidate the effect of different parts (fruit, leaves, and seed) of papaya on thrombocytopenia. For the Purpose, the papaya fruit, leaves, and seeds were procured from Botanical Garden of University of Agriculture Faisalabad. Afterwards, the papaya fruit, leaves, and seeds were converted to powder followed by extraction of polyphenol with various solvents (aqueous ethanol and methanol). The obtained extracts were characterized for total flavonoid contents, polyphenols as well as anti, nutritional compounds, such as tannins and saponins. Moreover, efficacy trials were carried out to explore the effect of papaya parts (fruit, leaves, and seed) on the platelets count of potassium bromate-induced (PBI) rats. The PBI rats were fed with extract enriched diet for a time period of 56 days. Results showed that maximum extraction was obtained with ethanol. In addition, a higher bioactive profile (polyphenols) was observed in papaya leaves extract followed by fruit and seed extracts. Papaya leaves extract (PLE) treatment showed a maximum increase in platelets count from 169.9 ± 2.1 × 10 9 /L to 231.1 ± 6.1 × 10 9 /L in PBI rats as well as WBCs and RBCs 521 ± 16.8 × 10 7 /L to 594.5 ± 11.2 × 10 7 /L and 469.2 ± 13.2 × 10 7 /L to 562.2 ± 14.2 × 10 7 /L. But for hemoglobin, the papaya fruit extract treatment showed a higher value of 6.4 ± 0.1 to 7.4 ± 0.2 (mg/dL). Conclusively, papaya leaves should be included in dietary regimens for health promotion to combat thrombocytopenia and related diseases.